New World Order Dan Dampaknya Terhadap Agama-Agama Semitik - Ribbel, Muhammad Aslam; Rohmatika, Ratu Vina (Universitas Islam Negeri Raden Intan Lampung, 2022)
The New World Order is a movement that is closely related to economic and political movements. But besides that, this movement also has an influence on the religious traditions of existing religions in order to achieve their goal, namely to form a new world order. This study aims to see the correlation between the new world order and the traditions in the teachings of religions, especially semitic religions. This research is a descriptive qualitative literature review. From this research, it is found that the new world order movement has an impact on religious beliefs by creating a new age movement. This movement is intended to create a new religious order that includes all religions by using theological liberalization. From it emerged various teachings and ideas that were contrary to the sacred doctrines of religions that originated from these revelations and holy books.